FRAMEWORK COBIT PADA DOMAIN APO02 DALAM TATA KELOLA TEKNOLOGI INFORMASI MANAGE STRATEGY - Annisa Hestiningtyas; Alva Hendi Muhammad; Asro Nasiri (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Information technology (IT) governance plays a crucial role in an organisation's success in leveraging Information Technology as a strategic asset. The COBIT (Control Objectives for Information and Related Technologies) framework has been widely recognised as an effective guide for Information Technology governance. One of the main domains in the COBIT framework is APO02 on Manage Strategy, which focuses on managing IT strategy in the context of holistic IT governance. The method used in writing the journal is a literature study of both books and journals related to the COBIT Framework. The purpose of writing this journal is to provide an overview and benefits of implementing the APO02 domain. These benefits include increased alignment between business and IT strategies, a better understanding of the value generated by IT, and improved data-based decision making and technological innovation. In addition, challenges that may arise in the implementation of APO02 domains, such as limited resources, rapidly changing business needs, and the complexity of developing a sustainable IT strategy.